2020
DOI: 10.1148/rg.2020190110
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Deposition and Nephrogenic Systemic Fibrosis: A Radiologist’s Primer

Abstract: Gadolinium-based contrast agents (GBCAs) have an excellent safety profile. However, over the last 2 decades, two specific concerns have surfaced. GBCAs are associated with nephrogenic systemic fibrosis (NSF) and tissue retention of gadolinium. NSF is a rare fibrosing disorder with a poor prognosis, which is characterized by skin and subcutaneous thickening as well as systemic manifestations. The disease has been reported exclusively in patients with advanced renal disease, and it is associated with higher dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 48 publications
2
103
0
6
Order By: Relevance
“…7,8 Additionally, DCE-MRI with gadolinium chelate increases the burdens on the patient in terms of potential for gadolinium retention and nephrogenic systemic fibrosis, examination time, and cost. [9][10][11][12][13][14] Therefore, interest is growing in performing abbreviated prostate MRI protocols without DCE-MRI, as a procedure termed "biparametric MRI" (bpMRI). 8 A number of studies on bpMRI using PI-RADS v2 have reported that the diagnostic accuracy of bpMRI for detecting csPC is comparable to that of mpMRI.…”
mentioning
confidence: 99%
“…7,8 Additionally, DCE-MRI with gadolinium chelate increases the burdens on the patient in terms of potential for gadolinium retention and nephrogenic systemic fibrosis, examination time, and cost. [9][10][11][12][13][14] Therefore, interest is growing in performing abbreviated prostate MRI protocols without DCE-MRI, as a procedure termed "biparametric MRI" (bpMRI). 8 A number of studies on bpMRI using PI-RADS v2 have reported that the diagnostic accuracy of bpMRI for detecting csPC is comparable to that of mpMRI.…”
mentioning
confidence: 99%
“…Recently, concern has been raised about gadolinium deposition in the brain, which is of unclear clinical significance and has been related to the number of contrast administrations as well as the use of linear GBCAs. 65 Although currently available aortic endografts have been individually classified as either conditional or safe for use in MRI, endograft material can influence study quality. MRA is more effective in the evaluation of nitinol stent grafts, as stainless steel and nickel alloys cause significantly more susceptibility artifact that may preclude optimal assessment.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…El depósito de gadolinio puede ocurrir en pacientes con función renal conservada y se asocia con mayor frecuencia a moléculas lineales por su menor estabilidad y mayor tasa de disociación en comparación con las moléculas de estructura macrocíclica (Kanda et al, 2015). Gadodiamida presenta una mayor tasa de depósito en el sistema nervioso central, seguido de Gadopentato de dimeglumina y Gadobenato de dimeglumina (Mathur et al, 2019). A pesar de no existir repercusiones clínicas conocidas, regulaciones internacionales como FDA y EMA recomiendan suspender el uso de medios de contraste basados en gadolinio de estructura química lineal.…”
Section: Depósito De Gadolinio En El Sistema Nervioso Centralunclassified